Beneficial Effect of Cissus quadrangularis Linn. on Osteopenia Associated with Streptozotocin-Induced Type 1 Diabetes Mellitus in Male Wistar Rats - Srinivasa Rao Sirasanagandla; Sreedhara Ranganath Pai Karkala; Bhagath Kumar Potu; Kumar M.R. Bhat (Hindawi Limited, 2014)
Petroleum ether fraction of Cissus quadrangularis (PECQ) impact on the development of osteopenia in type 1 diabetic rat model has been evaluated. Diabetic rats were treated orally with two doses of PECQ. Another group of diabetic rats were treated with subcutaneous injection of synthetic human insulin. The cortical and trabecular bone thickness and bone strength were significantly decreased in diabetic rats. Treatment with two doses of PECQ significantly prevented these changes in diabetic rats. However, PECQ treatment (two doses) did not alter the glycemic levels in these diabetic rats. Increased levels of serum alkaline phosphatase (ALP), tartrate-resistant acid phosphatase (TRAP), and hydroxyproline were noted in diabetic rats when compared to normal control rats. The two doses of PECQ treatment further improved the serum ALP levels and significantly decreased the serum levels of TRAP and hydroxyproline. The effects of PECQ treatment on histological, biomechanical, and biochemical parameters are comparable to those of insulin. Since PECQ improves the bone health in hyperglycemic conditions by enhancing the cortical and trabecular bone growth and altering the circulating bone markers, it could be used as an effective therapy against diabetes-associated bone disorders.